1ISG-015 Optimisation of biological therapies in the treatment of psoriasis. (March 2019) - Dominguez, A; Fernandez-Corada, A; Garcia, A; Gonzalez, S; Lopez, R; Blazquez, C; Labrador, N; Moya, P
Abstract : Background: The use of biological treatments for psoriasis involves a significant improvement in disease management. However, the economic impact of its use on health systems is high. Optimised treatment patterns of biological therapies, in clinically controlled patients, attempt to find a more efficient use of these drugs. Purpose: To analyse patients with psoriasis on an optimised pattern of biological treatment and to estimate the annual saving of these optimised patterns in a third-level hospital. Material and methods: Observational, retrospective and longitudinal study of psoriasis patients treated with biologic drugs in a general hospital of 650 beds. Medical records review and a retrospective analysis of prescriptions registered in the integral external Patient Information System and in the computerised History System was carried out up to 30 September 2018. We recorded demographic data (age, sex), type of biological therapy, clinical control of disease, optimised therapy yes/no and the annual economic impact due to every drug in an optimised pattern. Results: One hundred and fifty patients diagnosed with psoriasis were included, 102 (68%) men and 48 (32%) women, aged between 9 and 87 years (median 46.8 years). Patient distribution according to the biologic drug used, number of patients in optimised treatment patterns and the estimated saving per patient per year are included in table 1 . Forty-eight patients (32%) were in treatment with an optimised biological therapy pattern. It is estimated that with these optimised biological therapies the annual saving is around €1 60 000. Conclusion: The number of our patients receiving individualised biological treatment for psoriasis is more than one-third, which allows the same clinical effects with less economic impact on our health system. The estimated savings per year in our hospital due to optimised biological treatments for psoriasis is important because quality of treatment is not affected. References and/or acknowledgements: No conflict of interest.